Empowering Generation Z: The Influence of Self-Efficacy and Digital Financial Inclusion on Financial Behavior in the Digital Era - Chaniago, Sabaruddin; Nurul Syafiqah Azman; Ahmad Fadli; Deva Djohan; Widy Hastuty (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2025)
Effective Financial Self-Efficacy (EFSE) and Digital Financial Inclusion (DFI) significantly impact financial behavior, particularly among younger generations like Generation Z, who are increasingly familiar with digital financial services. This research seeks to examine the impact of EFSE on financial behavior (FB) using DFI within Generation Z in Medan City. A quantitative methodology was employed to gather data via an online survey of 147 Generation Z respondents who regularly utilize digital financial platforms, including digital wallets, mobile banking, and fintech loans. The Partial Least Squares–Structural Equation Modeling (PLS-SEM) method was used to examine the relationship between the proposed variables and analyze the data. The findings indicate that EFSE exerts a positive and significant impact on FB, with DFI serving as a mediator that enhances the influence of EFSE on financial behavior. These results indicate that Generation Z individuals with elevated financial self-efficacy are more judicious in their financial decision-making, particularly when facilitated by access to digital financial services. This study enhances the behavioral finance literature by emphasizing the essential roles of EFSE and DFI in cultivating sound financial practices among youth in the digital era. The findings indicate the necessity to create extensive digital and financial literacy initiatives to enhance self-efficacy and the use of digital financial services within Generation Z